Comunidades aquáticas do reservatório de Serra da Mesa (GO): distribuição, influências e a pesca esportiva sobre o tucunaré azul (Cichla piquiti) - Silva, Leo Caetano Fernandes da (2013)
The objective of this work was explore the relationships between diet, morphology and taxonomy in 30 species from Serra da Mesa Reservoir. The relationships between diet and morphology, diet and taxonomy and morphology e taxonomy were examined using Mantel test. And we test the relationships between diet and morphology after retire the effect os taxonomy using Partial Mantel Test. We used RDA to explore relevant attributes to diet. Results show that, independently of Taxonomy, some of the trophic guilds could be grossly predicted from few relevant morphological attributes (i.e mouth width and mouth Height especially for piscivores and carnivores) and thus suggest a significant link between diet and morphology. In other words, species having similar diet tend to converge to some extent on some morphological attributes.